A degradation–consolidation model for the stabilization behavior of landfilled municipal solid waste. (February 2020) - Chen, Y.M.; Xu, W.J.; Ling, D.S.; Zhan, L.T.; Gao, W.
Abstract: The stabilization behavior of landfilled municipal solid waste (MSW) plays an important role in the design, operation, and after care of landfills. The stabilization is dependent on the biological degradation and consolidation processes of landfilled MSW. A degradation–consolidation model for MSW was developed, which took biological degradation, skeleton deformation, two-phase flow, and solutes transport into consideration. In this model, the mass transformations of solid to liquid and then to gas were involved. The compression, hydraulic and solute transport material properties were related to the solid mass loss and the pore volume change. Indicators for the stabilization behavior of landfilled MSW were proposed. These indicators were calculated using the degradation–consolidation model to compare the stabilization behavior of landfilled high food waste content (HFWC) and low food waste content (LFWC) MSW. The results showed that the stabilization process of HFWC MSW landfills could be divided into rapid degradation, slow degradation, and post-stabilization stages based on the development of stabilization indicators. The normalized ratio of cellulose to lignin could be implemented to assess the stabilization stage of landfill more easily in practice.